ANALISIS TOKSIKOLOGI FORENSIK DAN INTERPRETASI TEMUAN ANALISIS - Agus Gelgel Wirasuta, Made (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 1 (2008): Indonesian Journal of Legal and Forensic Sciences, 2008)
Forensic toxicology is aplication of analytical chemistry to detects, identifies and determines of foreignchemicals and its metabolites in the body as legal evidances, and then make interpretaion or a testimony inestablishing the caouse of intoxication/death-cases. Step of analitical forensic (clinic) toxicoligy are: 1)sample preparation, 2) screening and determination test, 3) writing the interpretation of analitical finding intoa testimony. The result of screening test can be used as guindance that a person has been used an drugs, andthe result the determination test is a valid evidance for the interpretation and writing a testimony.
Keywords: Analytical toxicology forensic